NDM-1 carbapenemase in Acinetobacter baumannii sequence type 32 in Ecuador - J.E. Villacís; M. Bovera; D. Romero-Alvarez; F. Cornejo; V. Albán; G. Trueba; H.F. Dorn; J.A. Reyes (New Microbes and New Infections, 2019)
Objectives: To describe a clinical case of Acinetobacter baumannii sequence type (ST) 32 harbouring a New Delhi metallo-β-lactamase (NDM) in Ecuador. Methods: We used multilocus sequence typing (MLST) to confirm the bacterial species and the sequence type of an A. baumannii isolate. We used synergy with the imipenem–EDTA disc method and the carbapenem inactivation method (CIM) to determine carbapenemase production; the presence of a carbapenemase gene was confirmed by PCR amplification and amplicon sequencing. Results: Molecular characterization revealed the presence of A. baumannii ST32 harbouring the blaNDM-1 gene in Ecuador. The blaNDM-1 gene was isolated through PCR and amplified from a purified plasmid. Conclusions: To the best of our knowledge, this is the first report of A. baumannii ST32 harbouring the blaNDM-1 gene. Keywords: Acinetobacter baumannii, antibiotic resistance, blaNDM-1, MSLT, sequence type 32